The dose–response relationship between training-load measures and aerobic fitness in elite academy soccer players. Issue 2 (3rd April 2021) - Ellis, Matthew; Penny, Ryan; Wright, Ben; Noon, Mark; Myers, Tony; Akubat, Ibrahim
ABSTRACT: The aim of the current study is to examine the dose–response relationships between training load (TL) measures and the consequent changes in aerobic fitness. Data were collected over the 6-week pre-season period in elite youth soccer players. Participants completed a lactate threshold test to identify changes in treadmill speed at 2 mmol · l −1 (S2) and 4 mmol · l −1 (S4). Internal TL was quantified with the following training impulse (TRIMP) methods: Banister TRIMP, Edwards TRIMP, Lucia TRIMP, individual TRIMP (iTRIMP) and rate of perceived exertion was also collected. External TL measures were total distance, PlayerLoad, high speed running (14.4–19.8 km · h −1 ), very high-speed running (19.8–25.2 km · h −1 ) and maximal sprint distance (>25.2 km · h −1 ). Individual high-speed distance was derived from each participants treadmill speed at S4. Different Bayesian regression models were run with different likelihood functions. The best-fitting models with both the lowest out-of-sample prediction error and the highest variance explained ( R 2 ) were used. iTRIMP had the strongest relationships with changes in S2 (r = 0.93, R 2 = 0.90) and S4 (r = 0.88, R 2 = 0.82). Explained variance ranged from 10%–69% and 11%–38% for all other internal TL measures and external measures, respectively. In summary, the iTRIMP method demonstrates a dose–response relationship with changes in aerobic fitness in elite youth soccer players.